«Cose che imparerai meglio con l’uso e col criterio». Codificazione della norma interpuntiva in Italia e in Polonia - Foremniak, Katarzyna (Studia Romanica Posnaniensia, 2013)
The purpose of the article is to present the results of analysis regarding the processes of developing and standardizing the norm of punctuation in Poland and in Italy since the beginning of the 20th century to recent times. Aiming to describe the character of the two norms and to explain the differences between the Polish and the Italian rules, the study emphasizes the role of institutions in the codification process. Furthermore, it examines the typology of normative sources in both countries and comments the status of punctuation among other branches of linguistics.